Dermal Sinus with an Associated Dumbbell Dermoid Cyst: A Case Report - Scott, Hayden; Afuwape, Olusoji A.; Rice, Grace; Mehta, Sagar; Tanaka, Tomoko (Archives of Clinical and Medical Case Reports, 2021)
Abstract not available in the source database.